The influence of digital literacy on students' reading interest in indonesian language subjects - Sukandar, Eka; Arrahim, Arrahim; Dicky Dermawan, Deden (Elementary Teacher Education Program, Majalengka University, 2025)
The rapid development of digital technology has transformed the learning process, with digital literacy becoming a critical skill for students, including in primary schools. Digital literacy plays an important role in enabling students to access and utilise information from digital sources effectively, which in turn affects their learning outcomes. One aspect that is affected by digital literacy is students' reading interest, especially in Indonesian language subjects. This study aims to examine the relationship between digital literacy and reading interest in Indonesian subjects among third grade students of SDI Al Azhar 9, Bekasi. The research method used was a correlational quantitative research design. The population in this study were all third grade students of SDI Al Azhar 9, Bekasi, with a sample of 120 students selected randomly. Data collection was conducted through a Likert scale questionnaire that measured students' digital literacy and reading interest. Data analysis used descriptive and inferential statistics with Pearson correlation test to test the relationship between the two variables. The results showed that most students had a moderate level of digital literacy, while their reading interest was also moderate. Statistical analysis revealed a significant positive correlation between digital literacy and reading interest, with digital literacy explaining 52% of the variation in students' reading interest. This suggests that improving digital literacy can encourage greater reading interest. This study recommends that educators and parents guide students in using digital technology productively to improve their reading habits and academic performance.